The changed geopolitical map: Implications for business policy in a sustainable finance perspective - Pervez N. Ghauri; Lars Oxelheim; Trond Randøy (Research Institute of Industrial Economics (IFN), 2023)
The relationship between multinational enterprises (MNEs) and governments has evolved over time, from a period of conflict after World War II to a more cooperative relationship in the 1970s and 1980s (Dunning, 1993). In the 1990s, many host governments sought foreign direct investments (FDIs) by MNEs and subsidized inward investments through excessive locational competition (Oxelheim & Ghauri, 2004). However, recently, this relationship has changed again, and outward-oriented policies have been replaced by protectionist ones (Ghauri, Strange & Cooke, 2021; Oxelheim & Randøy, 2021). Home country governments, particularly in the US (i.e., Inflation Reduction Act) and in Europe (i.e., Net-Zero Industry Act as part of the Green Deal Industrial Plan), are concerned about technology transfers and value chain vulnerabilities from both inward and outward investments.
Keywords: D25; E22; E24; E58; E62; F21; F23; L22; 330; Sustainable finance; ESG; protectionism; globalization; state aid; investment patterns; global value chain